Students’ Critical Thinking on Reading Comprehension Based on Contextual Reading Material: An Experimental Study - Pratama, Aryawira; Putri , Regita Riani; Fitrah, Yundi (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
In this article, the researchers delve into the paramount role that critical thinking plays in the realm of reading comprehension, particularly for eighth-grader students who learned English in one of junior high schools in Jambi city. It is well-established that English language proficiency, especially in the domain of reading, is pivotal for students to access high-quality education and seize research opportunities. As we navigate the multifaceted landscape of education, it becomes evident that nurturing critical thinking skills among students is crucial for their academic and intellectual growth. The research undertaken herein embarks on a journey to explore the intricate connection between contextual reading materials and the development of student's critical thinking abilities. This endeavor involved a rigorous and systematic approach, employing a quasi-experimental research design that featured an experimental group and a control group. The outcomes of this investigation are of significant import, as they point to a compelling revelation: the utilization of contextual reading materials has a profound and positive impact on enhancing students' reading comprehension and fostering their critical thinking skills. These findings underscore the transformative potential of innovative pedagogical strategies that incorporate real-world context into the learning process, ultimately enriching the educational experience for students.